2015
DOI: 10.1364/oe.23.023133
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-angular-momentum crosstalk and temporal fading in a terrestrial laser link using single-mode fiber coupling

Abstract: Using a mobile experimental testbed, we perform a series of measurements on the detection of laser beams carrying orbital angular momentum (OAM) to evaluate turbulent channel distortions and crosstalk among receive states in an 84-m roofed optical link. We find that a receiver assembly using single-mode fiber coupling serves as a good signal selector in terms of crosstalk rejection. From the recorded temporal channel waveforms, we estimate average crosstalk profiles and propose an appropriate probability densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…where j S j is the sum of the intensities in all the modes, including mode i. Experimental results have shown that a Johnson-SB fading distribution is a good fit for OAM modes [91][92][93], however, there has been no work identifying how the (numerous) parameters of the Johnson-SB distribution map to standard variables such as C 2 n or r 0 . There has been no experimental work determining the fading distributions in real atmosphere for other higher-order mode sets such as the HG, IG or even LG modes where p = 0.…”
mentioning
confidence: 99%
“…where j S j is the sum of the intensities in all the modes, including mode i. Experimental results have shown that a Johnson-SB fading distribution is a good fit for OAM modes [91][92][93], however, there has been no work identifying how the (numerous) parameters of the Johnson-SB distribution map to standard variables such as C 2 n or r 0 . There has been no experimental work determining the fading distributions in real atmosphere for other higher-order mode sets such as the HG, IG or even LG modes where p = 0.…”
mentioning
confidence: 99%
“…The crosstalk fading h pq was demonstrated in [30] to obey a Johnson S B distribution. However, the latter distribution is analytically intractable which makes theoretical derivations not feasible.…”
Section: System Modelmentioning
confidence: 99%
“…For all the previous models, closed-form expressions for performance metrics such as the average capacity, the outage probability, and the bit-error rate (BER) were derived. In OAM FSO systems, to the best of our knowledge, the only proposed statistical channel models for turbulence-induced fading were given in [18], [19].…”
Section: Introductionmentioning
confidence: 99%